Young Generation Perceptions of Marriage: Analyzing the #MarryIsScary Hashtag on TikTok - Nabilah, Osha; Praptiningsih, Novi Andayani; Hermansah, Tantan; Fanshoby, Muhammad; Hayat, Heni (Institut Komunikasi dan Bisnis LSPR, 2024)
This study explores how the TikTok hashtag #MarryIsScary influences young people’s negative perceptions of marriage. As social media shapes public discourse, this research examines the role of TikTok in amplifying marriage-related anxieties. Using a qualitative digital ethnographic approach, this study analyzed 100 videos and 1,000 comments associated with #MarryIsScary to assess dominant narratives and user engagement. Findings indicate that 68% of videos portray marriage negatively, citing fears of commitment, financial burden, and emotional instability. Additionally, 60% of comments reinforce these concerns, reflecting a growing skepticism toward marriage, especially among women aged 18-30 years. TikTok’s algorithm further amplifies these views, fostering an echo chamber effect. The platform serves as both a public discourse space and a reinforcement mechanism for shifting social values. Young users actively engage in discussions that challenge traditional marital expectations, revealing evolving attitudes toward relationships and long-term commitments. To counterbalance negative marriage narratives, a creative educational approach is needed. Engaging, positive content can provide a more realistic perspective on marriage, supporting informed decision-making among young users.